Penggunaan Tanaman Mangrove Sebagai Obat Herbal di Lampung Selatan - Rodiani, Rodiani; Islamy, Nurul (CV. Jasa Sukses Abadi, 2024)
As a means of adaptation to extreme habitats, mangrove plants produce a variety of secondary metabolic substances that have the potential as herbal medicines. Empirically, coastal communities have utilized and proven the medicinal properties of mangrove plants. The study’s objective was to determine the use of mangrove plants as herbal medicine in Pematang Pasir, South Lampung. The use of mangroves as medicine was obtained through in-depth interviews followed by descriptive analysis and calculation of species use value, plant part value, and fidelity level. The results showed that the use of mangrove plants as herbal medicine in the Pematang Pasir area, Ketapang District, South Lampung, ethnically dominated by the Serang ethnic group (54%), with the majority having completed junior high school education (38.1%), economically classified as middle-income based on BPS criteria (2020), with the majority working as fishermen and farmers, and the majority being adults (over 40 years old). Based on the Species Use Value (SUV), R. apiculata is the most popular and widely used species by the community. Based on Plant Part Value (PPV) analysis, leaves are the most commonly used part as herbal medicine, with over 75% of the population using mangrove leaves as a source of treatment, while other parts are less utilized. The level of community trust in the benefits of mangrove plants as medicine is relatively low, with figures below 50%. Rhizophora apiculata is the only species accepted with a high level of confidence of 88%, particularly as a wound or antiseptic medicine.